TPE (thermoplastic elastomer) automobile composite foot pad and preparation process thereof

By using TPE composite materials and antibacterial agents in car foot pads, the problem of bacterial growth caused by rainwater during rainy days is solved, and the decontamination, water absorption and antibacterial properties are improved, ensuring a clean environment inside the car.

CN119119757APending Publication Date: 2024-12-13HIGHER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411529404.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing car foot pads will be contaminated with rainy days, causing bacteria to grow and affect the internal environment of the car.

Method used

The preparation process of TPE automobile composite foot pads is adopted, including TPE raw materials, polypropylene, SBS raw materials, calcium carbonate, stearic acid, paraffin oil, coupling agent, antioxidant, flame retardant, stabilizer, carbon nanotube, hydrophilic The composite material is formed by smelting and injection molding, and the surface is sprayed with antibacterial agents to improve antibacterial properties.

Benefits of technology

It improves the decontamination, water absorption and antibacterial properties of TPE automotive composite foot pads, extends the service life, enhances the protection of bacteria, and maintains the clean environment inside the car.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119757A_ABST
    Figure CN119119757A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of automobile composite foot pads, and discloses a TPE automobile composite foot pad and a preparation process thereof, the TPE automobile composite foot pad comprises a TPE raw material, polypropylene, an SBS raw material, calcium carbonate, stearic acid, paraffin oil, a coupling agent, acrylic acid, an antioxidant, a flame retardant, a stabilizer, carbon nanotubes, a hydrophilic additive, quaternary ammonium salt and nano titanium dioxide; the carbon nanotubes are added into the TPE composite material solution to improve the decontamination performance of the TPE composite material solution, the hydrophilic additive is put into the TPE composite material solution to improve the water absorption performance of the TPE composite material solution, and the quaternary ammonium salt and the nano titanium dioxide are put into the TPE composite material solution to improve the antibacterial performance of the TPE composite material solution. And after the TPE composite material solution is subjected to injection molding to form the TPE automobile composite foot pad, the surface of the TPE automobile composite foot pad is coated with a bacteriostatic agent, so that the bacteriostatic performance of the TPE automobile composite foot pad is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of automobile composite foot pads, in particular to a TPE automobile composite foot pad and a preparation process thereof. Background Art

[0002] With the popularity of cars, car mats have become an indispensable consumer product for people. At the same time, as people's living standards improve, people have more and more requirements for car mats. Comfort, beauty, environmental protection, dirt resistance, easy cleaning, safety and flame retardancy have become the hot spots of car mat industry research; Existing car floor mats are kept inside the car for a long time. On rainy days, the soles of passengers' shoes will be stained with rainwater. After the passengers get on the car, the rainwater will flow into the surface of the car floor mats. Since the car floor mats are kept inside the car for a long time, the rainwater on the car floor mats breeds a large number of bacteria, thereby affecting the environment inside the car. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a TPE automobile composite foot pad and a preparation process thereof, which solves the problems raised in the above background technology.

[0004] To solve the above technical problems, according to one aspect of the present invention, more specifically, a TPE automobile composite foot pad is prepared from TPE raw material, polypropylene, SBS raw material, calcium carbonate, stearic acid, paraffin oil, coupling agent, acrylic acid, antioxidant, flame retardant, stabilizer, carbon nanotubes, hydrophilic additives, quaternary ammonium salt and nano titanium dioxide.

[0005] Furthermore, the raw material of the automobile composite floor mat includes the following components in parts by weight: TPE raw material: 100 parts, polypropylene: 10-20 parts, SBS raw material: 20-25 parts, calcium carbonate: 1-5 parts, stearic acid: 3-7 parts, paraffin oil: 1 part, coupling agent: 8-15 parts, acrylic acid: 3-6 parts, antioxidant: 3-7 parts; flame retardant: 3-5 parts, stabilizer: 5-10 parts, carbon nanotubes: 1-5 parts, hydrophilic additive: 4-8 parts, quaternary ammonium salt: 1-3 parts, nano titanium dioxide: 1-2 parts.

[0006] Furthermore, the following steps are included: S1. 100 parts of TPE raw materials, 10-20 parts of polypropylene and 1 part of paraffin oil are placed in a mixing equipment and melted for 30 minutes, and then 20-25 parts of SBS raw materials, 1-5 parts of calcium carbonate and 3-7 parts of stearic acid are placed in a mixing equipment and melted for 20 minutes; S2, 8 to 15 parts of coupling agent by weight are placed in a mixing device for 5 minutes, and then 3 to 6 parts of acrylic acid, 3 to 7 parts of antioxidant and 3 to 5 parts of flame retardant are placed in the mixing device for 30 to 45 minutes, and then 5 to 10 parts of stabilizer are placed in the mixing device for 20 minutes; S3, 1-5 parts of carbon nanotubes by weight are placed in a mixing device for 15 minutes, and then 4-8 parts of hydrophilic additives are placed in a mixing device for 15 minutes, 1-3 parts of quaternary ammonium salts are placed in a mixing device for 15 minutes, and 1-2 parts of nano titanium dioxide are placed in a mixing device for 15 minutes; S4, placing the mixed TPE automobile composite material into an injection molding device, and injection molding the TPE automobile composite material into a TPE automobile composite foot pad through the injection molding device; S5. Place the TPE composite car floor mat into the spraying equipment, and spray the surface of the TPE composite car floor mat through the spraying equipment.

[0007] Furthermore, after the mixing equipment is melted, the calculation formula for the temperature required for the TPE automotive composite material solution to be kept warm is:

[0008] In the formula, is the temperature required for the TPE automotive composite material solution to be kept warm; R is the volume of the shell containing the TPE automotive composite material solution; m is the mass of the TPE automotive composite material solution; V is the volume of the TPE automotive composite material solution; Q is the heat absorbed or released by the TPE automotive composite material solution; The change of the solution temperature of TPE automotive composite material; The temperature of the TPE automotive composite solution after insulation; is the temperature of the TPE automotive composite material solution before insulation; T is the insulation time of the TPE automotive composite material solution; P is the temperature that the TPE automotive composite material solution needs to maintain; U is the thermal conductivity coefficient of the TPE automotive composite material solution; A is the total surface area of ​​the shell that accommodates the TPE automotive composite material solution; is the outdoor temperature; is the indoor temperature.

[0009] Furthermore, in S3, during the smelting of the hydrophilic additive, quaternary ammonium salt and nano-titanium dioxide, a stirring device with high temperature resistance is arranged inside the mixing device, and the TPE composite material, the hydrophilic additive, the quaternary ammonium salt and the nano-titanium dioxide are fully mixed during the smelting of the mixing device.

[0010] Furthermore, in S4, after the TPE automobile composite material is injection molded into a TPE automobile composite foot pad, the TPE automobile composite foot pad is placed in a dryer for drying for 2 to 4 hours, and the temperature of the dryer is set to 60°C.

[0011] Furthermore, in S5, the TPE automobile composite foot pad is placed in a spraying device, the spraying agent inside the spraying device is an antibacterial agent, and the spraying device sprays and covers the surface of the TPE automobile composite foot pad.

[0012] The beneficial effects of the TPE automobile composite foot pad and the preparation process thereof of the present invention are: The invention puts TPE raw material, polypropylene, SBS raw material, calcium carbonate, stearic acid, paraffin oil, coupling agent, acrylic acid, antioxidant, flame retardant and stabilizer into a mixing device for melting to form a TPE composite material solution, and adds carbon nanotubes into the TPE composite material solution to increase the decontamination performance of the TPE composite material solution, puts a hydrophilic additive into the TPE composite material solution to increase the water absorption performance of the TPE composite material solution, and then puts a quaternary ammonium salt and nano titanium dioxide into the TPE composite material solution to increase the antibacterial performance of the TPE composite material solution. After the TPE composite material solution is injection molded into a TPE automobile composite foot pad, an antibacterial agent is coated on the surface of the TPE automobile composite foot pad to further increase the antibacterial performance of the TPE automobile composite foot pad. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The present invention is further described in detail below with reference to the accompanying drawings and specific implementation methods.

[0014] Figure 1 It is a structural schematic diagram of the present invention. DETAILED DESCRIPTION

[0015] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.

[0016] like Figure 1 As shown, according to one aspect of the present invention, a TPE automobile composite foot pad is provided, which is prepared from TPE raw material, polypropylene, SBS raw material, calcium carbonate, stearic acid, paraffin oil, coupling agent, acrylic acid, antioxidant, flame retardant, stabilizer, carbon nanotubes, hydrophilic additives, quaternary ammonium salt and nano titanium dioxide.

[0017] In this embodiment, the raw materials of the automobile composite foot pad include the following components in parts by weight: TPE raw material: 100 parts, polypropylene: 10-20 parts, SBS raw material: 20-25 parts, calcium carbonate: 1-5 parts, stearic acid: 3-7 parts, paraffin oil: 1 part, coupling agent: 8-15 parts, acrylic acid: 3-6 parts, antioxidant: 3-7 parts; flame retardant: 3-5 parts, stabilizer: 5-10 parts, carbon nanotubes: 1-5 parts, hydrophilic additive: 4-8 parts, quaternary ammonium salt: 1-3 parts, nano titanium dioxide: 1-2 parts.

[0018] In this embodiment, the following steps are included: S1. 100 parts of TPE raw materials, 10-20 parts of polypropylene and 1 part of paraffin oil are placed in a mixing equipment and melted for 30 minutes, and then 20-25 parts of SBS raw materials, 1-5 parts of calcium carbonate and 3-7 parts of stearic acid are placed in a mixing equipment and melted for 20 minutes; S2, 8 to 15 parts of coupling agent by weight are placed in a mixing device for 5 minutes, and then 3 to 6 parts of acrylic acid, 3 to 7 parts of antioxidant and 3 to 5 parts of flame retardant are placed in the mixing device for 30 to 45 minutes, and then 5 to 10 parts of stabilizer are placed in the mixing device for 20 minutes; S3, 1-5 parts of carbon nanotubes by weight are placed in a mixing device for 15 minutes, and then 4-8 parts of hydrophilic additives are placed in a mixing device for 15 minutes, 1-3 parts of quaternary ammonium salts are placed in a mixing device for 15 minutes, and 1-2 parts of nano titanium dioxide are placed in a mixing device for 15 minutes; S4, placing the mixed TPE automobile composite material into an injection molding device, and injection molding the TPE automobile composite material into a TPE automobile composite foot pad through the injection molding device; S5. Place the TPE composite car floor mat into the spraying equipment, and spray the surface of the TPE composite car floor mat through the spraying equipment.

[0019] In this embodiment, after the mixing equipment is melted, the calculation formula for the temperature required for the TPE automotive composite material solution to be kept warm is:

[0020] In the formula, is the temperature required for the TPE automotive composite material solution to be kept warm; R is the volume of the shell containing the TPE automotive composite material solution; m is the mass of the TPE automotive composite material solution; V is the volume of the TPE automotive composite material solution; Q is the heat absorbed or released by the TPE automotive composite material solution; The change of the solution temperature of TPE automotive composite material; The temperature of the TPE automotive composite solution after insulation; is the temperature of the TPE automotive composite material solution before insulation; T is the insulation time of the TPE automotive composite material solution; P is the temperature that the TPE automotive composite material solution needs to maintain; U is the thermal conductivity coefficient of the TPE automotive composite material solution; A is the total surface area of ​​the shell that accommodates the TPE automotive composite material solution; is the outdoor temperature; is the indoor temperature.

[0021] In this embodiment, in S3, during the smelting of the hydrophilic additive, quaternary ammonium salt and nano-titanium dioxide, a stirring device with high temperature resistance is arranged inside the mixing device, and the TPE composite material, the hydrophilic additive, the quaternary ammonium salt and the nano-titanium dioxide are fully mixed during the smelting of the mixing device.

[0022] In this embodiment, in S4, after the TPE automobile composite material is injection molded into a TPE automobile composite foot pad, the TPE automobile composite foot pad is placed in a dryer for drying for 2 to 4 hours, and the temperature of the dryer is set to 60°C.

[0023] In this embodiment, in S5, the TPE composite car foot pad is placed in a spraying device, the spraying agent inside the spraying device is an antibacterial agent, and the spraying device sprays and covers the surface of the TPE composite car foot pad.

[0024] Example 1 S1, 100 parts of TPE raw materials, 10 parts of polypropylene and 1 part of paraffin oil were placed in a mixing equipment and melted for 30 minutes, and then 20 parts of SBS raw materials, 1 part of calcium carbonate and 3-7 parts of stearic acid were placed in a mixing equipment and melted for 20 minutes; S2, 8 parts of coupling agent by weight are placed in a mixing device for 5 minutes, and then 3 parts of acrylic acid, 3 parts of antioxidant and 3 parts of flame retardant are placed in the mixing device for 30-45 minutes, and then 5 parts of stabilizer are placed in the mixing device for 20 minutes; S3, placing 1 part of carbon nanotubes by weight into a mixing device for 15 minutes, then placing 4 parts of hydrophilic additives into the mixing device for 15 minutes, placing 1 part of quaternary ammonium salt into the mixing device for 15 minutes, and placing 1 part of nano titanium dioxide into the mixing device for 15 minutes; S4, placing the mixed TPE automotive composite material into an injection molding device, injection molding the TPE automotive composite material into a TPE automotive composite mat by the injection molding device, and then placing the TPE automotive composite mat into a dryer for drying for 2-4 hours, and the temperature of the dryer is set to 60°C; S5. Place the TPE composite car floor mat into the spraying equipment, and spray the antibacterial agent to cover the surface of the TPE composite car floor mat through the spraying equipment.

[0025] After the mixing equipment is melted, assuming that the volume R of the mixing equipment is 11L, the mass m of the TPE composite material solution is 13kg, the volume V of the TPE composite material solution is 10L, the heat Q absorbed by the PTE composite material solution is 100°C, and the temperature difference of the TPE composite material solution is The temperature of the TPE composite material solution after insulation is 20°C. The temperature of the TPE composite material solution before insulation is 120°C. The temperature of the TPE composite material solution is 80°C, the time T required for the TPE automotive composite material solution to be kept warm is 20 minutes, the temperature P that the TPE composite material solution needs to maintain is 100°C, the thermal conductivity coefficient U of the TPE composite material solution is 0.2W / (m·K), the surface area A of the inner wall of the mixing equipment is 1.13 cubic meters, and the indoor and outdoor temperature difference is 30°C; In summary, the formula is: 118, it can be concluded that the temperature required to maintain the TPE composite material solution after smelting is completed in this application is about 118°C.

[0026] Example 2 S1, 100 parts of TPE raw materials, 20 parts of polypropylene and 1 part of paraffin oil were placed in a mixing equipment and melted for 30 minutes, and then 25 parts of SBS raw materials, 5 parts of calcium carbonate and 7 parts of stearic acid were placed in a mixing equipment and melted for 20 minutes; S2, 15 parts of coupling agent by weight are placed in a mixing device for 5 minutes, and then 6 parts of acrylic acid, 7 parts of antioxidant and 5 parts of flame retardant are placed in the mixing device for 30-45 minutes, and then 10 parts of stabilizer are placed in the mixing device for 20 minutes; S3, 5 parts of carbon nanotubes by weight are placed in a mixing device for 15 minutes, and then 8 parts of hydrophilic additives are placed in a mixing device for 15 minutes, 3 parts of quaternary ammonium salts are placed in a mixing device for 15 minutes, and 2 parts of nano titanium dioxide are placed in a mixing device for 15 minutes; S4, placing the mixed TPE automotive composite material into an injection molding device, injection molding the TPE automotive composite material into a TPE automotive composite mat by the injection molding device, and then placing the TPE automotive composite mat into a dryer for drying for 2-4 hours, and the temperature of the dryer is set to 60°C; S5. Place the TPE composite car floor mat into the spraying equipment, and spray the antibacterial agent to cover the surface of the TPE composite car floor mat through the spraying equipment.

[0027] Comparative Example 1 The raw materials include the following components by weight: 100 parts of TPE, 15 parts of polypropylene, 36 parts of corn fiber, 8 parts of dioctyl phthalate, 5 parts of stearic acid, 8 parts of coupling agent, 15 parts of sodium hydroxide, 15 parts of magnesium hydroxide, 0.5 parts of paraffin oil, 5 parts of acrylic acid, and 5 parts of stabilizer; It also includes 6 parts of antistatic agent, which is an ionic surfactant; The coupling agent is a combination of silane coupling agent KH560 and silane coupling agent KH570.

[0028] Comparative Example 2 The raw materials include the following components by weight: 100 parts of TPE, 15 parts of polypropylene, 36 parts of corn fiber, 8 parts of dioctyl phthalate, 5 parts of stearic acid, 8 parts of coupling agent, 15 parts of sodium hydroxide, 15 parts of magnesium hydroxide, 0.5 parts of paraffin oil, 5 parts of acrylic acid, 5 parts of stabilizer, and 1 part of color powder; It also includes 18 parts of bamboo fiber and 9 parts of soy fiber; The weight ratio of corn fiber, bamboo fiber and soybean fiber is 2:1:0.5; It also includes 6 parts of antistatic agent, which is an ionic surfactant; The coupling agent is a combination of silane coupling agent KH560 and silane coupling agent KH570.

[0029] Comparative Example 3 In parts by weight, the raw materials include the following components: 100 parts of TPE, 20 parts of polypropylene, 34 parts of corn fiber, 9 parts of dioctyl phthalate, 7 parts of stearic acid, 10 parts of coupling agent, 17 parts of sodium hydroxide, 17 parts of magnesium hydroxide, 0.8 parts of paraffin oil, 6 parts of acrylic acid, 6 parts of stabilizer, and 3 parts of color powder; It also includes 17 parts of bamboo fiber and 8.5 parts of soybean fiber; The weight ratio of corn fiber, bamboo fiber and soybean fiber is 2:1:0.5; It also includes 6 to 8 parts of an antistatic agent, which is an ionic surfactant; The coupling agent is a combination of silane coupling agent KH550 and silane coupling agent KH570.

[0030] Comparative Example 4 In parts by weight, the raw materials include the following components: 100 parts of TPE, 25 parts of polypropylene, 30 parts of corn fiber, 10 parts of dioctyl phthalate, 8 parts of stearic acid, 12 parts of coupling agent, 20 parts of sodium hydroxide, 20 parts of magnesium hydroxide, 1 part of paraffin oil, 8 parts of acrylic acid, 8 parts of stabilizer, and 5 parts of color powder; It also includes 15 parts of bamboo fiber and 7.5 parts of soybean fiber; The weight ratio of corn fiber, bamboo fiber and soybean fiber is 2:1:0.5; It also includes 8 parts of antistatic agent, which is an ionic surfactant; The coupling agent is a combination of silane coupling agent KH550 and silane coupling agent KH560.

[0031] Comparative Example 5 15 parts of polypropylene, 36 parts of corn fiber, 8 parts of dioctyl phthalate, 5 parts of stearic acid, 8 parts of coupling agent, 15 parts of sodium hydroxide, 15 parts of magnesium hydroxide, 0.5 parts of paraffin oil, 5 parts of acrylic acid, and 5 parts of stabilizer were stirred at 60°C and 20 rpm for 1 hour, and finally 100 parts of TPE were added, and the mixture was mixed on a rubber mixer at 160°C for 5 minutes; The weight ratio of corn fiber, bamboo fiber and soybean fiber is 2:1:0.5; The mixture further comprises 6 parts of an antistatic agent, which is an ionic surfactant. The antistatic agent is stirred for 1 hour at a temperature of 60° C. and a stirring rate of 20 rpm; The coupling agent is a combination of silane coupling agent KH560 and silane coupling agent KH550.

[0032] Comparative Example 6 20 parts of polypropylene, 34 parts of corn fiber, 9 parts of dioctyl phthalate, 7 parts of stearic acid, 10 parts of coupling agent, 17 parts of sodium hydroxide, 17 parts of magnesium hydroxide, 0.8 parts of paraffin oil, 6 parts of acrylic acid, 6 parts of stabilizer, and 3 parts of color powder were stirred at 90°C and 10 rpm for 1 hour, and finally 100 parts of TPE were added, and the mixture was mixed on a rubber mixer at 200°C for 3 minutes; The weight ratio of corn fiber, bamboo fiber and soybean fiber is 2:1:0.5; The mixture further comprises 8 parts of an antistatic agent, which is an ionic surfactant. The antistatic agent is stirred for 0.5 h at a temperature of 90° C. and a stirring rate of 10 rpm; The coupling agent is a combination of silane coupling agent KH560 and silane coupling agent KH570.

[0033] Comparative Example 7 25 parts of polypropylene, 30 parts of corn fiber, 10 parts of dioctyl phthalate, 8 parts of stearic acid, 12 parts of coupling agent, 20 parts of sodium hydroxide, 20 parts of magnesium hydroxide, 1 part of paraffin oil, 8 parts of acrylic acid, 8 parts of stabilizer, 5 parts of color powder were stirred at 75°C and 15 rpm for 0.7h, and finally 100 parts of TPE were added, and the mixture was mixed on a rubber mixer at 180°C for 4 minutes; The weight ratio of corn fiber, bamboo fiber and soybean fiber is 2:1:0.5; The mixture further comprises 7 parts of an antistatic agent, which is an ionic surfactant. The antistatic agent is stirred for 0.7 h at a temperature of 75° C. and a stirring rate of 15 rpm; The coupling agent is a combination of silane coupling agent KH550 and silane coupling agent KH570.

[0034] The tensile strength, elongation at break, absolute deformation, decontamination performance, water absorption performance and antibacterial performance of the TPE automotive composite foot pads prepared in the comparative example and the comparative example were tested. The specific data are shown in Table 1 Table 1

[0035] like Figure 1 As shown, the TPE automotive composite foot pad prepared by the present invention has similar tensile strength, elongation at break and absolute deformation data as those of Comparative Example 1 and Comparative Example 2, and far exceeds Comparative Example 3, Comparative Example 4, Comparative Example 5, Comparative Example 6 and Comparative Example 7. At the same time, the TPE composite foot pad prepared by the present invention is superior to Comparative Example 1 and Comparative Example 2 in terms of decontamination performance, water absorption performance and antibacterial performance.

[0036] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention also fall within the protection scope of the present invention.

Claims

1. A TPE automotive composite mat, characterized in that: The automobile composite foot pad is prepared from TPE raw material, polypropylene, SBS raw material, calcium carbonate, stearic acid, paraffin oil, coupling agent, acrylic acid, antioxidant, flame retardant, stabilizer, carbon nanotube, hydrophilic additive, quaternary ammonium salt and nano titanium dioxide.

2. The TPE automotive composite mat according to claim 1, characterized in that: The raw materials of the automobile composite foot pad include the following components in parts by weight: TPE raw material: 100 parts, polypropylene: 10-20 parts, SBS raw material: 20-25 parts, calcium carbonate: 1-5 parts, stearic acid: 3-7 parts, paraffin oil: 1 part, coupling agent: 8-15 parts, acrylic acid: 3-6 parts, antioxidant: 3-7 parts; flame retardant: 3-5 parts, stabilizer: 5-10 parts, carbon nanotube: 1-5 parts, hydrophilic additive: 4-8 parts, quaternary ammonium salt: 1-3 parts, nano titanium dioxide: 1-2 parts.

3. The preparation process of a TPE automobile composite foot pad according to claim 1, characterized in that: The following steps are involved: S1. 100 parts of TPE raw materials, 10-20 parts of polypropylene and 1 part of paraffin oil are placed in a mixing equipment and melted for 30 minutes, and then 20-25 parts of SBS raw materials, 1-5 parts of calcium carbonate and 3-7 parts of stearic acid are placed in a mixing equipment and melted for 20 minutes; S2, 8-15 parts of coupling agent by weight are placed in a mixing device for 5 minutes, 3-6 parts of acrylic acid, 3-7 parts of antioxidant and 3-5 parts of flame retardant are placed in a mixing device for 30-45 minutes, and 5-10 parts of stabilizer are placed in a mixing device for 20 minutes; S3, 1-5 parts of carbon nanotubes by weight are placed in a mixing device for 15 minutes, and then 4-8 parts of hydrophilic additives are placed in a mixing device for 15 minutes, 1-3 parts of quaternary ammonium salts are placed in a mixing device for 15 minutes, and 1-2 parts of nano titanium dioxide are placed in a mixing device for 15 minutes; S4, placing the mixed TPE automobile composite material into an injection molding device, and injection molding the TPE automobile composite material into a TPE automobile composite foot pad through the injection molding device; S5. Place the TPE composite car floor mat into the spraying equipment, and spray the surface of the TPE composite car floor mat through the spraying equipment.

4. The preparation process of a TPE automotive composite foot pad according to claim 3, characterized in that: After the mixing equipment is melted, the calculation formula for the temperature required for the TPE automotive composite material solution to be kept warm is: In the formula, is the temperature required for the TPE automotive composite material solution to be kept warm; R is the volume of the shell containing the TPE automotive composite material solution; m is the mass of the TPE automotive composite material solution; V is the volume of the TPE automotive composite material solution; Q is the heat absorbed or released by the TPE automotive composite material solution; The change of the solution temperature of TPE automotive composite material; The temperature of the TPE automotive composite solution after insulation; is the temperature of the TPE automotive composite material solution before heat preservation; T is the heat preservation time of the TPE automotive composite material solution; P is the temperature that the TPE automotive composite material solution needs to maintain; U is the thermal conductivity coefficient of the composite material solution; A is the total surface area of ​​the shell that contains the TPE automotive composite material solution; is the outdoor temperature; is the indoor temperature.

5. The preparation process of a TPE automobile composite foot pad according to claim 3, characterized in that: In S3, during the smelting of the hydrophilic additive, quaternary ammonium salt and nano-titanium dioxide, a stirring device with high temperature resistance is arranged inside the mixing device, and the TPE composite material, the hydrophilic additive, the quaternary ammonium salt and the nano-titanium dioxide are fully mixed during the smelting of the mixing device.

6. The preparation process of a TPE automotive composite foot pad according to claim 3, characterized in that: In S4, after the TPE automobile composite material is injection molded into a TPE automobile composite foot pad, the TPE automobile composite foot pad is placed in a dryer for drying for 2 to 4 hours, and the temperature of the dryer is set to 60°C.

7. The preparation process of a TPE automobile composite foot pad according to claim 3, characterized in that: In S5, the TPE automobile composite foot pad is placed in a spraying device, the spraying agent inside the spraying device is an antibacterial agent, and the spraying device sprays and covers the surface of the TPE automobile composite foot pad.